The Socio-economic Impact Of The Squid Stock Volatility In The Eastern Cape Province Of South Africa - Mthembu, Senzo Peter (School of Economics, 2020)
This is an ongoing paper that discusses the socio-economics of three neighbouring small towns (Humansdorp, St. Francis and Jeffreys Bay) in the Eastern Cape of South Africa, each largely dependent on the squid fishery. The paper addresses four issues: (1) the operations of the squid industry in South Africa; (2) the local impacts of its operations; (3) the financial stability of the industry and (4) the manner in which the resource and the industry are managed by the ministry (and the implications of this). The linkages of the squid industry into both the local and provincial economies are estimated using mixed data from existing survey and census statistics, and from qualitative interviews and questionnaires. The paper also describes the roles played by industry participants in the squid value chain. A key element in the debates surrounding the management of marine resources is the benefits they provide for previously disadvantaged populations. The paper unravels some of the complexities underpinning this issue, in particular concerns regarding resource rights, management through closed seasons, and control over value chains. The stability and geographical origins of affected communities are focal issues. The paper also identifies major costs of industry operations and roughly quantifies them as a preliminary to establishing linkages to the local economy. It is noted that although the different vessels in operation vary in size and cost, the basic technology used is similar. The return on capital depends, therefore, on the skills of the fishers and the health of the resource.